¿ Y el pluralismo teórico? - Cepeda, Margarita (Pontificia Universidad Católica del Perú, 2005)
The paper deals with the problem of theorelical pluralism, in the light of Dr. Hamer's case. founder of the New Medicine. After questioning the relationship between justice and pluralism as conceived of by contemporary politica liberalism, the paper defends an alternative of a hermeneutical type akin to Geertz's position versus Rorty's. which would counterbalance the typical reactionary position of every form of established knowledge.

El artículo se ocupa del problema del pluralismo teórico a la luz del caso del doctor Hamer, fundador de la Nueva Medicina. Después de cuestionar las relaciones entre justicia y pluralismo tal como las concibe el liberalismo político contemporáneo, el artículo defiende una alternativa de corte hermeneutico afín a la posición de Geertz contra Rorty, la cual serviría de contrapeso a la posición reaccionaria típica de toda forma de saber establecida.
And what about theoretical pluralism?
Keywords: Pluralism; Theory; Justice; Hermeneutics.; Pluralismo; Teoría; Justicia; Hermenéutica.; https://purl.org/pe-repo/ocde/ford#6.03.01